Study the Thermal Analysis of Materials Used in Insulation Pipelines - Mohammed A. M. Saed; Abdelhamid Issa Hwwili; M. H. Abdulali; Sulayman Y. Sulayman (African Journal of Advanced Pure and Applied Sciences, 2025)
The goal of the study is to examine and evaluate the various insulating materials utilized in pipelines. The study focused on the tubes used by Libyan Norwegian Fertilizers Company in order to determine how the insulator affected the quantity of heat loss and to determine the most cost-effective form of insulation. The research was conducted using the MATLAB application R2014a, and the data came from the reports utilized by the Libyan-Norwegian enterprise. Additionally, the thermal conductivity of insulating materials was measured using a Lee’s disk experiment. According to the findings, rock wool may be the most cost-effective and ideal option for insulation, but it has a drawback in that it is toxic. The study investigates the thermal analysis of insulation pipeline materials and alloys using a Lee’s disk experiment to measure various insulation materials (such as rock wool and camel skin) using a MATLAB computer program.